If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 = 9 + 3u Solving 48 = 9 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. 48 + -3u = 9 + 3u + -3u Combine like terms: 3u + -3u = 0 48 + -3u = 9 + 0 48 + -3u = 9 Add '-48' to each side of the equation. 48 + -48 + -3u = 9 + -48 Combine like terms: 48 + -48 = 0 0 + -3u = 9 + -48 -3u = 9 + -48 Combine like terms: 9 + -48 = -39 -3u = -39 Divide each side by '-3'. u = 13 Simplifying u = 13
| 4=6u-2 | | 4+11k=103 | | 30*32*9= | | 6-3u=18 | | 12*3.14= | | -16=3z+5 | | 5*3.14= | | 11*3.14= | | -20=7-3q | | 9*3.14= | | 10x+4x=126 | | 9n-3(2n-1)=12 | | SV+2=52 | | 2k+1=19 | | 7*3.14= | | 4z+4=32 | | 6*3.14= | | 4x-2(3y-5)= | | 450*5.25*2.5= | | 5-3*K=19 | | 3x=44-9x | | 6x^2+24=0 | | 15x=27+12x | | 9+11x=29+9x | | 17x-3=16x+9 | | 8x+6=5x+36 | | 5x+3.5=8 | | 5x^2+4xy*5y^2=0 | | 6x+17=41 | | a+(a+1)+(a+2)=72 | | 8x+14=38 | | 7x-(-10)=-39 |